β2-adrenergic receptor signaling regulates metabolic pathways critical to myeloid-derived suppressor cell function within the TME - Mohammadpour, Hemn; MacDonald, Cameron R.; McCarthy, Philip L.; Abrams, Scott I.; Repasky, Elizabeth A. (Cell reports (Cambridge), 2021)
Myeloid-derived suppressor cells (MDSCs) impede antitumor immunity; however, the precise mechanisms that regulate their suppressive function remain unresolved. Identifying these mechanisms could lead to therapeutic interventions to boost cancer immunotherapy efficacy. Here, we reveal that β2 adrenergic receptor (β2-AR) expression on MDSCs increases with tumor growth and that the β2-AR stress pathway drives the immune suppressive activity of MDSCs by altering their metabolism. We show that β2-AR signaling decreases glycolysis and increases oxidative phosphorylation and fatty acid oxidation (FAO). It also increases expression of the fatty acid transporter CPT1A, which is necessary for the FAO-mediated immunosuppressive function of MDSCs. Moreover, we show that β2-AR signaling increases autophagy and activates the arachidonic acid cycle, both required for increasing the release of the immunosuppressive mediator, PGE2. Our data reveal that β2-AR signaling triggered by stress is an important physiological regulator of key metabolic pathways in MDSCs, driving their immunosuppressive function. [Display omitted] •Tumor progression increases the expression of β2-AR on MDSCs•β2-AR signaling increases fatty acid oxidation and oxidative phosphorylation in MDSCs•β2-AR signaling in MDSCs increases autophagy-mediated PGE2 production Mohammadpour et al. show that β2-AR signaling in MDSCs alters their metabolic state and increases their immunosuppressive function. Specific processes found to be increased include fatty acid oxidation, oxidative phosphorylation, and autophagy. In addition, these metabolic alterations facilitate an increase in PGE2 production via elevated COX2 expression.